MBAH MUNAWAR, TASAWUF DAN KELESTARIAN LINGKUNGAN - Zuhri, Amat (Jurnal Penelitian, 2010)
As ’khalifa fi al-ardi’, mankind has responsibility to organize and settle many issues and resolve many problems laid down on the earth. To fulfill these duties, they are equiped with sense of mind and intelligence. Nowadays, through science and technology, rush and massive exploitation of resources are being uncontrolled day by day. So, this behavior creates some global crisis in many areas, including ecological disasters. This behavior, assumed, proceeded from the thoughts of mechanics-materialistic paradigms. On the contrary, tasawuf leads mankind to new enlighted paradigm and perspective in viewing world: not centre on material orientation; but spiritual one. A good example of tasawuf attitude was set by Mbah Munawar living in Karanggondang of Pekalongan. Eventhough, he has never learned tasawuf, his behavior -what he do- is reflecting tasawuf thoughts: zuhud, fanâ, baqâ, ittihâd, hulul, nur muhammad, insân kâmil and wahda/t/ al-wujud. In fact, despite of surrounding with the wealthy of natural capital, he doesn’t want to explore it exessively, but wisely and friendly